An investigation on the impact of natural disasters on global supply chains - Nornaim Sufyan Mohd Shairi. (2012)
As the world is becoming increasingly connected through globalization, businesses of today are constantly reviewing their supply chain policies to remain competitive in the industry. Through diversification of resources, plant location and production methods, businesses are increasingly geared towards satisfying customer needs along the supply chain. There is however, a silent but inevitable danger that natural disasters pose to these global supply chains.